Determinants of banking system fragility: a regional perspective - Hans Degryse; Muhammad Ather Elahi; María Fabiana Penas (European Central Bank (ECB), 2013)
We study the role of regional banking system characteristics for regional banking system fragility in Asia, Europe, Latin America and the US. We find that regional banking system fragility reduces when banks in the region jointly hold more liquid assets, are better capitalized, and when regional banking systems are more competitive. For Asia and Latin-America, a greater presence of foreign banks and more wholesale funded banks also reduces regional banking fragility. In contrast, regional banking fragility increases in foreign bank presence and wholesale funding in the US. We further investigate the possibility of contagion across regions. We find that the contagion effects of Europe and the US on Asia and Latin America are significantly higher compared to the effect of Asia and Latin America among themselves. Finally, the impact of cross-regional contagion is attenuated when the host region has a more liquid and more capitalized banking sector.
Keywords: G15; G20; G29; 330; Banking system stability; cross-regional contagion; financial integration